Morley's categoricity theorem : a survey. - Huang, Leonard Tristan Zhiliang. (2008)
The report serves as a survey of one of the most important theorems in Model Theory - Morley's Categoricity Theorem. The tools and techniques which go into the proof will be discussed in depth and the overall strategy will be made clear.